Spatiotemporal Processing in Crossmodal Interactions for Perception of the External World: A Review - Hidaka, Souta; Teramoto, Wataru; Sugita, Yoichi (Frontiers in Integrative Neuroscience, 2015)
Research regarding crossmodal interactions has garnered much interest in the last few decades. A variety of studies have demonstrated that multisensory information (vision, audition, tactile sensation, and so on) can perceptually interact with each other in the spatial and temporal domains. Findings regarding crossmodal interactions in the spatiotemporal domain (i.e., motion processing) have also been reported, with updates in the last few years. In this review, we summarize past and recent findings on spatiotemporal processing in crossmodal interactions regarding perception of the external world. A traditional view regarding crossmodal interactions holds that vision is superior to audition in spatial processing, but audition is dominant over vision in temporal processing. Similarly, vision is considered to have dominant effects over the other sensory modalities (i.e., visual capture) in spatiotemporal processing. However, recent findings demonstrate that sound could have a driving effect on visual motion perception. Moreover, studies regarding perceptual associative learning reported that, after association is established between a sound sequence without spatial information and visual motion information, the sound sequence could trigger visual motion perception. Other sensory information, such as motor action or smell, has also exhibited similar driving effects on visual motion perception. Additionally, recent brain imaging studies demonstrate that similar activation patterns could be observed in several brain areas, including the motion processing areas, between spatiotemporal information from different sensory modalities. Based on these findings, we suggest that multimodal information could mutually interact in spatiotemporal processing in the percept of the external world and that common perceptual and neural underlying mechanisms would exist for spatiotemporal processing.